Promoting social engagement for young adults living in social isolation in Sweden: social workers and health care professionals' perceptions of success factors. Issue 1 (2nd January 2023) - Ayoub, Maria; Udo, Camilla; Randell, Eva
ABSTRACT: The number of young adults not in employment, education or training has increased globally and socially withdrawn young people have proven difficult to support. Therefore, this study aimed to explore what factors social workers and health care professionals find more successful in supporting socially withdrawn young adults. Semi-structured interviews were conducted in 2018 with 13 employees (nine women, four men between 35 and 60 years) from social services and outpatient psychiatric clinics in Sweden. Data were analysed using thematic network analysis. The results revealed that the participants tended to associate the issues of young adults with difficulties related to transition into adulthood and that successful factors to re-engage these young adults were based on an empowerment-oriented perspective. The focus needed to be on the young individual's strengths and interventions had to be conducted in collaboration with different authorities (e.g. social services, employment agencies and schools). This study shows that a successful intervention to break the isolation of socially withdrawn young adults and meet their complex needs calls for early identification, an integrated and holistic approach, multifaceted interventions and individually tailored and flexible activities.